USE OF A SPIRITUALITY SELF-RATING SCALE IN PATIENTS WITH KIDNEY DISEASE UNDERGOING HEMODIALYSIS - Ana Lúcia Rodrigues Correia; Islene Victor Barbosa; Francisca Elisângela Teixeira Lima; Virna Ribeiro Feitosa Cestari; Rita Mônica Borges Studart; Francisca Lígia de Medeiros Martins (Universidade Federal do Paraná, 2015)
The present study aimed to assess the spiritual well-being of patients undergoing hemodialysis, based on a Spirituality Self-Rating Scale for use in health care. Cross-sectional descriptive study with 80 patients hospitalized to treat kidney disease undergoing hemodialysis. Data collected from December 2011 to January 2012, through a self-rating scale for assessment of spirituality. Of the 80 patients, 93.75% had some religious belief. Regarding the expressions of spirituality, 57.5% agreed with the expression "My spiritual/religious beliefs give a meaning to my life"; 70%, with the expression "My faith and belief give me strength at difficult times"; 48.8%, with "I have hope in the future"; 21.3% with "I feel my life has changed for the better"; and 63.7%, with "I learned to appreciate the little things in life". It has been observed that the spiritual/religious aspect has great influence on the health status of patients with kidney disease undergoing hemodialysis, highlighting the importance for health professionals to be prepared for dealing with this issu.